2000
DOI: 10.1007/bf03184475
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady aerodynamic loads on high speed trains passing by each other

Abstract: In order to study unsteady aerodynamic loads on high speed trains passing by each other 350km/h, three-dimensional flow fields around trains during the crossing event are numerically simulated using three-dimensional Euler equations. Roe's FDS with MUSCL interpolation is employed to simulate wave phenomena. An efficient moving grid system based on domain decomposition techniques is developed to analyze the unsteady flow field induced by the restricted motion of a train on a rail. Numerical simulations of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…For example, the magnitude and rate of change of the pressure pulse, side force, and overturning moment increase dramatically. Therefore, to ensure the safety of two trains passing each other, full-scale tests [4,5], moving model tests [6][7][8], and computational fluid dynamics (CFD) simulations [2,3,9] have been performed to investigate the aerodynamic performance of the trains. It was found that parameters including the train speed, line spacing, nose shape, and marshalling length affect the aerodynamic performance of the passing trains.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the magnitude and rate of change of the pressure pulse, side force, and overturning moment increase dramatically. Therefore, to ensure the safety of two trains passing each other, full-scale tests [4,5], moving model tests [6][7][8], and computational fluid dynamics (CFD) simulations [2,3,9] have been performed to investigate the aerodynamic performance of the trains. It was found that parameters including the train speed, line spacing, nose shape, and marshalling length affect the aerodynamic performance of the passing trains.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation and characteristics of the air wave in a railway tunnel caused by the passage of a train or passing trains have increasingly aroused great academic and engineering concerns in rail transport. [1][2][3][4][5] With the increased speed of trains, the magnitude of the initial pressure rise generated around the car body becomes much larger than that in the open sections; this unsteady aerodynamic loading may destabilize the trains (i.e. the car body is in a state of sway and yawing motion), and thus cause larger running vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations of the strain passing by on the double-track were carried out to study the effect of the train nose-shape, length and the existence of a tunnel on the crossing event. [2]. RA MacNeill et al described a set of experiments designed to gather pressure-time histories on a tall, large surface area double-stack container car as a high-speed train passes [3] .…”
Section: Introductionmentioning
confidence: 99%